DEVELOPMENT OF STUDENTS' CREATIVE ABILITIES THROUGH DIGITAL TECHNOLOGIES IN PRIMARY EDUCATION IS AN IMPORTANT PEDAGOGICAL PROBLEM (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
Developing students’ creative abilities through digital technologies in primary education is considered one of the pressing issues in contemporary pedagogy. This article analyzes existing scientific and literary sources, identifying gaps and under-researched aspects within the topic. It explores innovative approaches aimed at activating primary students' thinking via digital tools, guiding them toward creative problem-solving, and enhancing their didactic engagement. Based on pedagogical experimentation, the study examines the practical possibilities and effectiveness of applying digital technologies, as well as their role in fostering independent thinking and creative approaches among learners. The methodology section outlines data collection methods including observation, surveys, and experimental testing, while the results section presents their analysis and graphical representation. In the discussion, the author presents theoretical conclusions, practical recommendations, proposed solutions to existing problems, and promising directions for future research based on the findings.